Social responsibility and green practices in organizational performance: Corporate image as mediating mechanism - Rodrigues, Rosa Isabel; Teixeira, Natalia; Luis, Ana Lucia; Silva, Rui (International Journal of Management and Sustainability, 2023)
Sustainability-related endeavors are progressively employed to cultivate a favorable business reputation that enhances consumer loyalty and, as a result, enhances organizational performance. This study is situated within a specific research issue and seeks to examine the mediating function of corporate image in the association between social and moral responsibility, green practices in the workplace, and organizational performance. The study sample consisted of 223 individuals who were employed as workers, ranging in age from 18 to 64 years. The study was operationalized using a quantitative methodology. Data were collected through four questionnaires assessing employees’ perceptions of social and moral responsibility, green practices in the workplace, corporate image, and the performance of the organization where they work. The results revealed that social and moral responsibility, green practices in the workplace, and corporate image have a significant positive influence on organizational performance. It was also found that when corporate image enters the model with the status of a mediating variable, the effect of social and moral responsibility on organizational performance decreases but remains significant. These results suggest that when organizational performance is evaluated, the importance attributed to corporate image overlaps with social and moral responsibility. This research highlights the importance of cultivating a positive corporate image. It also helps to increase perceptions of the organization’s social and environmental responsibility and to strengthen customer loyalty by improving its reputation and fostering higher levels of trust. These improvements can subsequently increase sales, boost profits, and expand the organization’s market share.